Rice Export and Its Effect on Gross Domestic Product in Nigeria: 2000 – 2023 - Idisi, Park O.; Adeagbo, Benjamin A.; Maduekwe, Innocent M.; Isike, Glory O.; Olaniyan, Abdullahi A.; Achemu, David O.; Isah, Mariam; Ifeaghalu, Maryjane I.; Salako, Akinniyi O.; Adeyemi, Mohammed F. (European Scientific Journal, ESJ, 2026)
This study examined the effect of rice export on Nigeria’s Gross Domestic Product (GDP) using annual time series data covering the period 2000 to 2023. The study employed trend analysis, Ordinary Least Squares (OLS) regression, and the Autoregressive Distributed Lag (ARDL) model to analyze the relationship among rice export, exchange rate, and GDP. Unit root tests using the Augmented Dickey Fuller procedure revealed that all variables were stationary at level, implying that they are integrated of order zero I(0). The trend analysis indicated that exchange rate and rice export exhibited a positive trend over the study period, while GDP showed fluctuations across the years. The OLS regression results revealed that exchange rate had a positive but statistically insignificant effect on GDP (p > 0.05), while rice export also showed a positive but insignificant relationship with GDP. The ARDL estimation further showed that the lagged value of GDP had a positive and statistically significant effect on current GDP (p < 0.05). Exchange rate demonstrated a positive relationship with GDP and was weakly significant at the 10 percent level (p < 0.10), whereas rice export remained statistically insignificant. The Granger causality test revealed a unidirectional causal relationship running from exchange rate to GDP. The findings concludes that although rice export has growth potential, its current contribution to Nigeria’s GDP remains limited. The study therefore recommends policies aimed at improving rice productivity, export competitiveness and value chain development to enhance the role of agricultural exports in economic growth.